Culture in the American Southwest : The Earth, the Sky, the People - Bryant, Keith L. (Book collections on Project MUSE., 2014)
If the Southwest is known for its distinctive regional culture, it is not only the indigenous influences that make it so. As Anglo Americans moved into the territories of the greater Southwest, they brought with them a desire to reestablish the highest culture of their former homes: opera, painting, sculpture, architecture, and literature. But their inherited culture was altered, challenged, and reshaped by Native American and Hispanic peoples, and a new, vibrant cultural life resulted. From Houston to Los Angeles, from Tulsa to Tucson, Keith L. Bryant traces the development of ""high culture."